The Effectiveness of Worksheet Based Learning of Rotational Dynamics on Students’ Critical Thinking Skills Viewed from IQ Score - Herni Yuniarti Suhendi; Diah Mulhayatiah; Rizki Zakwandi (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
The aim of this study is to find out and analyze the effect of a worksheet based learning of rotational dynamics on students’ critical thinking skills viewed from IQ score and the correlation between critical thinking skills and the students’ IQ score. This research has been conducted in even semester of the academic year of 2017/2018, in university in Bandung area. All students in a university in Bandung City are the population for this study with the target population are all students in the first year in the university year of 2017/2018. The sample in this study is the first semester of Physics Education students as an experimental group, selected using purposive sampling technique, with data collecting tool in the form of written test of critical thinking skill and IQ. The research design used is one shot case design. A hypothesis test is done by using correlation and regression. The whole test of this data analysis used SPSS program. The results of this study indicate that the learning-based student's worksheet on the concept of Rotational Dynamics significantly influences students' critical thinking skills. It can be seen from the score of n-gain which is 0.5. Based on the calculation on correlation obtained value of 0.185 <0.5, it means that  IQ scores correlated weakly to the students’ critical thinking score, while the regression value of 0.303> 0.05, in other words, the students’ IQ score does not affect the students’ critical thinking skills. So it can be concluded that there is no correlation between IQ and critical thinking skills which seen from the results of correlation and regression analysis.